Mental health of migrants with pre-migration exposure to armed conflict: a systematic review and meta-analysis. (May 2022) - Mesa-Vieira, Cristina; Haas, Andreas D; Buitrago-Garcia, Diana; Roa-Diaz, Zayne M; Minder, Beatrice; Gamba, Magda; Salvador, Dante; Gomez, Daniel; Lewis, Meghann; Gonzalez-Jaramillo, Wendy C; Pahud de Mortanges, Aurélie; Buttia, Chepkoech; et al.
Summary: Background: Exposure to armed conflict has been associated with negative mental health consequences. We aimed to estimate the prevalence of generalised anxiety disorder, major depressive disorder, and post-traumatic stress disorder among migrants exposed to armed conflict. Methods: In this systematic review and meta-analysis, we searched online databases (Cochrane Library, Embase, LILACS, PsycInfo [via Ovid], PubMed, and Web of Science Core Collection) for relevant observational studies published between Jan 1, 1994, and June 28, 2021. We included studies that used standardised psychiatric interviews to assess generalised anxiety disorder, major depressive disorder, or post-traumatic stress disorder among migrants (refugees or internally displaced persons; aged ≥18 years) with pre-migration exposure to armed conflict. We excluded studies in which exposure to armed conflict could not be ascertained, studies that included a clinical population or people with chronic diseases that can trigger the onset of mental disease, and studies published before 1994. We used a random effects model to estimate each mental health disorder's pooled prevalence and random effects meta-regression to assess sources of heterogeneity. Two independent reviewers assessed the risk of bias for each study using the Joanna Briggs Institute Checklist for Prevalence Studies. The protocol was registered with PROSPERO, CRD42020209251. Findings: Of the 13 935 studies identified, 34 met our inclusion criteria; these studies accounted for 15 549 migrants. We estimated a prevalence of current post-traumatic stress disorder of 31% (95% CI 23–40); prevalence of current major depressive disorder of 25% (17–34); and prevalence of generalised anxiety disorder of 14% (5–35). Younger age was associated with a higher prevalence of current post-traumatic stress disorder (odds ratio 0·95 [95% CI 0·90–0·99]), lifetime post-traumatic stress disorder (0·88 [0·83–0·92]), and current generalised anxiety disorder (0·87 [0·78–0·97]). A longer time since displacement was associated with a lower lifetime prevalence of post-traumatic stress disorder (0·88 [0·81–0·95]) and major depressive disorder (0·81 [0·77–0·86]). Migrating to a middle-income (8·09 [3·06–21·40]) or low-income (39·29 [11·96–129·70]) country was associated with increased prevalence of generalised anxiety disorder. Interpretation: Migrants who are exposed to armed conflict are at high risk of mental health disorders. The mental health-care needs of migrants should be assessed soon after resettlement, and adequate care should be provided, with particular attention paid to young adults. Funding: Marie Skłodowska-Curie Actions (Horizon 2020—COFUND), MinCiencias (Colombia), and Swiss National Science Foundation.